Children and Career Interruptions: The Family Gap in Denmark - Nabanita Datta Gupta; Nina Smith (Institute for the Study of Labor (IZA), 2001)
The effect of children and career interruptions on the family gap is analysed based on Danish longitudinal data covering the years 1980-1995. The estimated model controls for unobserved time-constant heterogeneity. The results show that when controlling for unobserved heterogeneity, the negative effect of children on mothers? wages disappears. The main effect of children seems to be loss of human capital accumulation during childbirth periods. Beside this, there is no indication that children have long-term effects on the earnings potential of their mothers, holding experience constant.
Keywords: J9; 330; Children; career interruptions; family gap; unobserved heterogeneity; Frauenerwerbstätigkeit; Erwerbsverlauf; Erziehungsurlaub; Bildungsertrag; Schätzung; Dänemark